Genetic instability and associated genome plasticity in Streptomyces ambofaciens: pulsed-field gel electrophoresis evidence for large DNA alterations in a limited genomic region. - Leblond, P (1991)
Using pulsed-field gel electrophoresis (PFGE) analysis, the amplifiable units of DNA (AUD) loci AUD6 and AUD90 of Streptomyces ambofaciens DSM40697 could be mapped in the wild-type genome within two adjacent AseI restriction fragments estimated to be about 75 and 850 kb. In addition, the genetic instability and formation of very large deletions were strictly correlated. Their sizes were estimated to range from 250 to more than 2,000 kb. These deletions affected the DNA region overlapping both amplifiable loci. PFGE also allowed us to localize the amplified DNA sequences and to establish their structure: amplification takes place at the AUD locus as a tandem array of the wild-type AUD sequence.